Integrating Local Culture into Early Literacy through Storybook Development for Children - Febiola, Anisa; Aryanti, Nurul; Heriani, Dian (Fakultas Ilmu Budaya, Universitas Brawijaya, 2025)
This study analyzes the ability of children's storybook writing, supported by cultural integration programs, to effectively promote local heritage preservation through early literacy. This study emphasizes the creation of a storybook titled